Análise da viabilidade técnica e econômica da utilização de biogás em motores de ignição por compressão para geração de energia elétrica - Policena, Italo Rosa (2019)
Growth in energy demand and security of energy supply have become a concern in recent decades. The high cost of fossil fuels and the need to reduce the emission of greenhouse gases have made renewable energy sources attractive to the world economy. In this context, biomass becomes interesting, since it is the second largest source of renewable energy in Brazil and when converted to biofuels can have many characteristics similar to fossil fuels. The objective of this work was to analyze the technical and economic viability of the dualfuel combustion by fumigation and dualfuel by controlled reactivity (RCCI) methods in compression ignition engines, seeking the maximum substitution of diesel by biogas and having as purpose the generation of electric energy. The results showed that there are no penalties regarding the performance of the engine. Substitution values were higher than 94% at medium and high loads, and higher than 56% at low loads. Regarding the brake efficiencies, higher values were obtained in medium and high loads for the two combustion methods, with few changes in low loads. Regarding the economic analysis, the operation in dual-mode can bring a 40% greater economy when compared to the conventional diesel combustion. An applied study showed that a small rural bovine and pig farm can become self-sufficient in terms of electric energy, having a monthly internal rate of return of 3.11% and payback time in 27 months, showing that combustion in dual mode of biogas can be rather a source of energy at low cost in agriculture.